Analisis Algoritma Round Robin pada Penjadwalan CPU: Algoritma Scheduling CPU - Tri Dharma Putra; Rakhmat Purnomo (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2021)
ABSTRACT. Scheduling is a key concept in computer multitasking and multiprocessing operating system design and in real-time operating system design by switching the CPU among process. Round Robin Algorithm is a wellknown algorithm in CPU scheduling. Round Robin Algorithm provides a time quantum between context switching. Choosing the time quantum in Round Robin Algorithm is very crucial, large quantum time will result in lower context switching, while small quantum time wil result in higher context switching. For waiting time, the idea for waiting time is to get smaller waiting time which is more efficient. Turn around time also should be minimum, which is more efficient. Two case studies are discussed to understand this algorithm more deeply. We did analysis with data set process 1 till process 5 (P1-P5), with burst time dataset: 20ms, 34ms, 25ms, 62ms, 67ms. In case study 1, we use quantum 25m, and in case study 2, we use quantum 15ms. Context switching in case study 2 is 17 where on case study 1, only 10 context switchings. Total burst-time in case study 1 and case study 2 are 208 ms. Average waiting time in case study 1 is 82 ms, where in case study 2 is 105.8 ms. Average Turn Around Time in case study 1 is 123.6ms, where in case study 2 is 146.6 ms. Keywords: Round Robin Algorithm, quantum time, context switching, average waiting time, average turn around time